2021
DOI: 10.1016/j.celrep.2021.109392
|View full text |Cite
|
Sign up to set email alerts
|

LYSMD3: A mammalian pattern recognition receptor for chitin

Abstract: Highlights d Human airway epithelial cells display the receptor LYSMD3 on their surface d LYSMD3 contains a LysM (chitin-binding) domain and is able to bind chitin and fungi d Chitin and fungi fuel cytokine release by binding LYSMD3 on airway epithelial cells d LYSMD3 also binds b-glucan and therefore may also sense b-glucan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
0
18
1
Order By: Relevance
“…activation of multiple different human innate immune cell types and stimulation of adaptive immune responses. Compared to earlier results, chitin oligomers thus not only possess a strong capacity to fully signal danger to epithelial 11 and myeloid innate cell types (e.g. macrophages, PMNs) 10, 15 but also to lymphoid innate immune cells such as NK cells.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…activation of multiple different human innate immune cell types and stimulation of adaptive immune responses. Compared to earlier results, chitin oligomers thus not only possess a strong capacity to fully signal danger to epithelial 11 and myeloid innate cell types (e.g. macrophages, PMNs) 10, 15 but also to lymphoid innate immune cells such as NK cells.…”
Section: Resultscontrasting
confidence: 70%
“…Additionally, we identified the innate immune receptor Toll-like receptor (TLR2) as a primary fungal chitin sensor on human and murine myeloid cells {Fuchs, 2018 #9694} and the host chitinase CHIT1 as an enzyme involved in oligomer generation 10 . Illustrating the validity of using pure chitin oligomers, He and colleagues have also shown that chitin oligomers can be recognized by the Lysin motif (LysM)-domain containing receptor LYSMD3 on the surface of human airway epithelial cells and elicit production of inflammatory cytokines 11 . However, so far the effects of oligomeric chitin on lymphoid innate (NK cells) and adaptive (B and T lymphocytes) immune cells have not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In these organisms, chitin is a model microbe-associated molecular pattern (MAMP), as evidenced by the existence of chitin-mediated activation of immune responses through pattern recognition receptors (PRRs) [5,6]. Chitin is sensed through the receptor CERK1 and its co-receptor CEBiP in plants [7] [8] and in humans by Tolllike receptor (TLR) 2 in immune cells [9] and by FIBCD1 or LYSMD3 on epithelial cells [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In these organisms, chitin is a model microbe-associated molecular pattern (MAMP), as evidenced by the existence of chitin-mediated activation of immune responses through pattern recognition receptors (PRRs) [5, 6]. Chitin is sensed through the receptor CERK1 and its co-receptor CEBiP in plants [7] [8] and in humans by Toll-like receptor (TLR) 2 in immune cells [9] and by FIBCD1 or LYSMD3 on epithelial cells [10, 11]. However, during initial exposure, the mammalian host encounters chitin in a highly polymeric and insoluble form of exoskeleton particles of house dust mites or the cell wall of pathogenic fungi, have a form that has been considered immunologically inert [4].…”
Section: Introductionmentioning
confidence: 99%
“…Mannans are also recognized by host cells [28] and may also provide a barrier to limit access of fungicidal molecules to the plasma membrane [31]. The full role of chitin in recognition of C. albicans at the host epithelia is unclear and the subject of ongoing research [32], but it has been shown that purified C. albicans chitin upregulates production of the antiinflammatory cytokine IL-10 in macrophages [33]. The rearrangement of the cell wall due to stress and other stimuli (i.e., treatment with a cell-surface damaging antifungal drug) can result in changes in the distribution of all 3 components at the cell surface and can cause unmasking of β-1,3 glucan [34].…”
Section: Introductionmentioning
confidence: 99%